2021
DOI: 10.3390/agronomy11010112
|View full text |Cite
|
Sign up to set email alerts
|

Morpho-Physiological Characterization of Diverse Rice Genotypes for Seedling Stage High- and Low-Temperature Tolerance

Abstract: Extreme temperatures are considered one of the main constraints that limit the growth and development of rice. We elucidated the root and shoot developmental plasticity of 64 rice genotypes during early seedling establishment, using the sunlit plant growth chambers at 22/14 (low), 30/22 (optimum), and 38/30 °C (high) day/night temperatures. Low temperature severely inhibited 23 traits, such as shoot (68%), root (57%), and physiological (35%) attributes. On the contrary, the high temperature positively affected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 59 publications
1
21
1
Order By: Relevance
“…In contrast with the present results, previous studies have demonstrated that decreasing plant growth temperature significantly increased the chlorophyll index [41,42]. Many studies have utilized the plant chlorophyll index as a metric for characterizing the plant's tolerance to multiple abiotic stresses, especially temperature stress in grain and vegetables [41,43,44]. Low temperature significantly increased the non-destructive TCI of basil leaves by 18%.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast with the present results, previous studies have demonstrated that decreasing plant growth temperature significantly increased the chlorophyll index [41,42]. Many studies have utilized the plant chlorophyll index as a metric for characterizing the plant's tolerance to multiple abiotic stresses, especially temperature stress in grain and vegetables [41,43,44]. Low temperature significantly increased the non-destructive TCI of basil leaves by 18%.…”
Section: Discussioncontrasting
confidence: 99%
“…Understanding the relationship between growth and developmental, physiological, and yield-related traits and other contributing characters helps maximum breeding gain from a selection. The additive vigor indices are a reliable method of assessing the growth rate and development of genotype performance under fluctuating environmental conditions (Reddy et al, 2021). Here, we show how the additive response index can help identify relationships between morpho-physiological and yield-related traits of rice genotypes under non-stress conditions.…”
Section: Introductionmentioning
confidence: 91%
“…Under non-stress conditions, the average number of days to 50% emergence (when three seeds emerged out of six) varied from 8 to 12 days after planting. Emergence could be a useful trait in selecting vigorous genotypes for breeding early seedling stage heat and drought tolerance (Reddy et al, 2021). Most of the rice genotypes usually germinate within a week.…”
Section: Phenotypic Variationmentioning
confidence: 99%
“…Meanwhile, low temperature weakens the process of dry matter synthesis and transformation, resulting in a prolonged growth period, and nally reduces the rice yield (Shimono et al 2007). 15°C low temperature stress decreases rice tillering, especially for the temperature-sensitive rice varieties, and 12°C has a strong depression on tillering for even insensitive varieties (Liu et al 2019;Reddy et al 2021). Moreover, the depression effect of low temperature on rice tillering is associated with the duration of the low temperature, that is to say the longer the low temperature lasts, the more harmful it is to rice tiller number and growth rate (Liu et al 2019;Sperotto et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Rice is the most important food crop, feeding almost 1/2 of the human population (Pittol et al 2018;Zhang et al 2017), while rice is sensitive to low temperature (Ma et al 2015;Reddy et al 2021). Global climate change has led to frequent occurrence of low temperature damage, which ultimately reduces rice yield (Dar et al 2021;Pandit et al 2017;Pradhan et al 2019).…”
Section: Introductionmentioning
confidence: 99%